2012
DOI: 10.1128/aac.01197-12
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activities of Iron Chelators against Common Nosocomial Pathogens

Abstract: The activities of iron chelators (deferoxamine, deferiprone, Apo6619, and VK28) were evaluated against type strains of Acinetobacter baumannii, Pseudomonas aeruginosa, Staphylococcus aureus, Klebsiella pneumoniae, and Escherichia coli. Deferiprone, Apo6619, and VK28 each inhibited growth in standard and RPMI tissue culture medium, while deferoxamine had no effect. Additionally, time-kill assays revealed that VK28 had a bacteriostatic effect against S. aureus. Therefore, these newly developed iron chelators mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
99
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(108 citation statements)
references
References 25 publications
5
99
0
4
Order By: Relevance
“…Multiple studies conducted by prominent laboratories have demonstrated that iron or zinc limitation can suppress Acinetobacter growth and that the organisms have multiple iron and zinc acquisition mechanisms, including catechol production, production of very high-affinity siderophores (e.g., acinetobactin) and companion siderophore uptake receptor and energetic mechanisms, and heme utilization (82,121,(308)(309)(310)(311)(312)(313)(314)(315)(316)(317)(318)(319)(320). Small-molecule iron chelators have in vitro activity at killing Acinetobacter during log growth (318). Thus, combatting iron or zinc uptake in the bacteria is a novel, potentially impactful therapeutic approach.…”
Section: Trace Metal Sequestrationmentioning
confidence: 99%
“…Multiple studies conducted by prominent laboratories have demonstrated that iron or zinc limitation can suppress Acinetobacter growth and that the organisms have multiple iron and zinc acquisition mechanisms, including catechol production, production of very high-affinity siderophores (e.g., acinetobactin) and companion siderophore uptake receptor and energetic mechanisms, and heme utilization (82,121,(308)(309)(310)(311)(312)(313)(314)(315)(316)(317)(318)(319)(320). Small-molecule iron chelators have in vitro activity at killing Acinetobacter during log growth (318). Thus, combatting iron or zinc uptake in the bacteria is a novel, potentially impactful therapeutic approach.…”
Section: Trace Metal Sequestrationmentioning
confidence: 99%
“…These bacteria were also tested for sensitivity to the FDA-approved iron chelators DFP and DFX and an iron chelator commonly used in the research laboratory, DIP. DFP and DFX are compounds that are used to treat iron overload in humans and also demonstrate the ability to restrict the growth of bacteria in vitro (12). The MIC 90 s of all of the antibiotics and chelators tested could be reliably determined (see Table S1).…”
Section: Resultsmentioning
confidence: 93%
“…Because an estimated 30% of all enzymes require metals as a cofactor and iron is critical for such cellular events as DNA biosynthesis, the trichloroacetic acid cycle, oxidative stress defense, and energy transduction (7,9,10), targeting of iron-dependent processes represents a viable strategy for antimicrobial development. Indeed, there are a growing number of studies evaluating the use of iron chelators as antibacterials, with efficacy demonstrated in some cases (11)(12)(13) but not others (14,15). Inspired by the way mammals restrict bacterial growth to prevent infection (16,17), we report here that the combined use of iron chelators and sublethal concentrations of some antibiotics generates a potent response that kills the cells of a model Gram-negative blood pathogen (extraintestinal pathogenic Escherichia coli [ExPEC]).…”
mentioning
confidence: 99%
“…Установлено, что хелатор железа VK28 обладает бактериоста-тическим действием на бактерии Staphylococcus aureus [46]. Таким образом, препараты, хелатирующие же-лезо, в частности деферипрон и деферасирокс, по-казаны при инфекционных заболеваниях, вызван-ных антибиотикорезистентными возбудителями, и при инфекциях у пациентов с синдромом пере-грузки железом.…”
Section: хелаторы железа (сидерофоры)unclassified